Czy Łódź Piotrowa wpłynęła do stoczni remontowej? Kościół u schyłku pontyfikatu papieża Franciszka – w stronę podsumowania - Kościelniak, Cezary (Człowiek i Społeczeństwo, 2022)
The purpose of the article is to summarize the pontificate of Pope Francis in the period between 2013–2022. The context of the analysis is the follow: how is the Church going through the processes of renewal, and reforms and what impact is it having? The text focuses on the issues: the peripheralization of the Church, the world of open borders, ecology and the Pope’s criticism of Europe.